Extending total parenteral nutrition hang time in the neonatal intensive care unit: Is it safe and cost effective?. Issue 1 (17th December 2012) - Balegar V, Kiran Kumar; Azeem, Mohammad Irfan; Spence, Kaye; Badawi, Nadia
<x xml:space="preserve">Abstract</x> Aim To investigate the effects of prolonging hang time of total parenteral nutrition (TPN) fluid on central line–associated blood stream infection (CLABSI), TPN‐related cost and nursing workload. Methods A before–after observational study comparing the practice of hanging TPN bags for 48 h (6 February 2009–5 February 2010) versus 24 h (6 February 2008–5 February 2009) in a tertiary neonatal intensive care unit was conducted. The main outcome measures were CLABSI, TPN‐related expenses and nursing workload. Results One hundred thirty‐six infants received 24‐h TPN bags and 124 received 48‐h TPN bags. Median (inter‐quartile range) gestation (37 weeks (33, 39) vs. 36 weeks (33, 39)), mean (±standard deviation) admission weight of 2442 g (±101) versus 2476 g (±104) and TPN duration (9.7 days (±12.7) vs. 9.9 days (±13.4)) were similar (P > 0.05) between the 24‐ and 48‐h TPN groups. There was no increase in CLABSI with longer hang time (0.8 vs. 0.4 per 1000 line days in the 24‐h vs. 48‐h group; P < 0.05). Annual cost saving using 48‐h TPN was AUD 97 603.00. By using 48‐h TPN, 68.3% of nurses indicated that their workload decreased and 80.5% indicated that time spent changing TPN reduced. Conclusion Extending TPN hang time from 24 to 48 h did not alter CLABSI rate and was associated with a reduced TPN‐related cost and perceived nursing workload. Larger randomised controlled trials are needed to more clearly delineate these effects.